PHILOSOPHY OF SCIENCE AS THE HISTORICAL BASIS OF THE DEVELOPMENT OF SCIENCE AND KNOWLEDGE - Lubis, Muya Syaroh Iwanda; Fitri, Anisa (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2023)
ABSTRACTPhilosophy is an extensive science, meaning it is closely related to our daily lives, and philosophy is the driving force of our daily lives as individual human beings and as collective human beings in the form of a society or nation. Philosophy of science is a philosophical reflection on the nature of science which will not recognize a stopping point towards achieving the goal, namely truth and reality. Understanding the philosophy of science means understanding the intricacies of science so that its most essential aspects and foundations also understand the perspective of science, the possibility of its development, and its interweaving between one branch of science and another. The research approach that researchers use in writing this scientific work is a type of library research. Philosophy is a science that seriously studies the true nature of everything. Science is a method of thinking objectively in describing and giving meaning to the natural and moral world to organize and systematize. Knowledge indicators are: It is accumulative, and its truth is not absolute but objective. There are six phases of scientific development: The Pre-Ancient Greece Phase, the Ancient Greek Phase, the Medieval Age Phase, the Renaissance Age phase, the Modern Age phase, and finally, the Contemporary Age phase. Keywords: Philosophy, Historical, Development, Science, Knowledge